2017
DOI: 10.1177/1010428317701624
|View full text |Cite
|
Sign up to set email alerts
|

UBC®RapidTest for detection of carcinoma in situ for bladder cancer

Abstract: UBC Rapid Test is a test that detects fragments of cytokeratins 8 and 18 in urine. We present results of a multicentre study measuring UBC Rapid Test in bladder cancer patients and healthy controls with focus on carcinoma in situ (CIS) and high-grade bladder cancer. From our study with N = 452 patients, we made a stratified sub-analysis for carcinoma in situ of the urinary bladder. Clinical urine samples were used from 87 patients with tumours of the urinary bladder (23 carcinoma in situ, 23 non-muscle-invasiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 40 publications
5
31
0
Order By: Relevance
“…This is in accordance with other reports showing sensitivities in the range of 53–64% and specificities in the range of 63–91% [ 46 , 47 , 48 , 49 , 50 , 51 ]. Similar to survivin, UBC ® Rapid also has a higher sensitivity for high-grade tumors [ 46 , 50 , 51 , 52 ] in comparison to low-grade tumors, indicating that the UBC ® Rapid test may be more useful for this subgroup. The test may be influenced by urinary tract infections as has been shown before [ 53 ].…”
Section: Discussionsupporting
confidence: 94%
“…This is in accordance with other reports showing sensitivities in the range of 53–64% and specificities in the range of 63–91% [ 46 , 47 , 48 , 49 , 50 , 51 ]. Similar to survivin, UBC ® Rapid also has a higher sensitivity for high-grade tumors [ 46 , 50 , 51 , 52 ] in comparison to low-grade tumors, indicating that the UBC ® Rapid test may be more useful for this subgroup. The test may be influenced by urinary tract infections as has been shown before [ 53 ].…”
Section: Discussionsupporting
confidence: 94%
“…1 ), a total of 14 potential relevant articles were identified initially, of which four were removed subsequent to reading the titles and abstracts in further detail. Following a full-text review, two studies were eliminated due to lack of sufficient data, leaving eight studies ( 14 16 , 22 , 31 34 ). The basic characteristics of the studies are summarized in Table I .…”
Section: Resultsmentioning
confidence: 99%
“…These cytokeratins are located in the cytoskeleton of epithelial cells and tend to be overexpressed in urothelial tumor types including bladder cancer ( 17 19 ). Based on this, several trials have been performed to investigate the efficacy of the UBC ® Rapid Test in the detection and follow-up of bladder cancer ( 20 22 ). However, differences in the design and enrollment of these studies have resulted in inconsistent conclusions, so its diagnostic accuracy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies reported the diagnostic ability of proteins cytokeratin and 18 using the UBC Rapid point of care Omega 100 reader [63][64][65][66] A combination of urinary cytology, midkine (NEGF2) and gamma synuclein quantification using ELISA reported a ROC of 0.949 with a sensitivity and specificity of 91.8% and 97.5% respectively 27 . The nonsulfated glycosaminoglycan hyaluronic acid (HA) quantified by ELISA reported a sensitivity and specificity of 88% and 82% increasing to 90% and 84% respectively when combined with hyaluronidase, a catalytic enzyme that degrades HA 21 .…”
Section: Protein Biomarkersmentioning
confidence: 99%